2013
DOI: 10.1038/cddis.2013.143
|View full text |Cite
|
Sign up to set email alerts
|

Yeast techniques for modeling drugs targeting Bcl-2 and caspase family members

Abstract: Development of drugs targeting Bcl-2 relatives and caspases, for treating diseases including cancer and inflammatory disorders, often involves measuring interactions with recombinant target molecules, and/or monitoring cancer cell killing in vitro. Here, we present yeast-based methods for evaluating drug-mediated inhibition of Bcl-2 relatives or caspases. Active Bax and caspases kill Saccharomyces cerevisiae, and pro-survival Bcl-2 proteins can inhibit Bax-induced yeast death. By measuring the growth or adenos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
5
13
0
Order By: Relevance
“…9 In addition, flow cytometry analysis showed that NK4 could induce apoptosis and cell cycle arrest at G0/G1 in RA-FLS and MH7A cells. 15 In the present study, we found that NK4 decreased Bcl-2 protein level and increased Bax and cleaved caspase 3 protein levels, indicating an essential role of NK4 in the induction of the apoptosis of RA-FLS and MH7A cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…9 In addition, flow cytometry analysis showed that NK4 could induce apoptosis and cell cycle arrest at G0/G1 in RA-FLS and MH7A cells. 15 In the present study, we found that NK4 decreased Bcl-2 protein level and increased Bax and cleaved caspase 3 protein levels, indicating an essential role of NK4 in the induction of the apoptosis of RA-FLS and MH7A cells.…”
Section: Discussionsupporting
confidence: 63%
“…The activation of caspase 3 is the key to cause apoptosis . Antiapoptotic Bcl‐2 and proapoptotic Bax belong to Bcl‐2 family and are the main regulators of caspase activation pathway during apoptosis . In the present study, we found that NK4 decreased Bcl‐2 protein level and increased Bax and cleaved caspase 3 protein levels, indicating an essential role of NK4 in the induction of the apoptosis of RA‐FLS and MH7A cells.…”
Section: Discussionsupporting
confidence: 59%
“…As previously described for the human and/or murine orthologs (Ink et al, 1997;Tao et al, 1997;Ligr et al, 1998), expression of canine Bak and Bax showed a lethal effect in yeast. Moreover, this effect was abrogated on co-expression of the anti-apoptotic members Bcl-xL, Mcl-1 and Bcl-w as previously demonstrated for large part of their human orthologs in yeast (Tao et al, 1997;Beaumont et al, 2013). To our knowledge, abrogation of the effect of Bak by Bcl-w has not been previously reported in this model.…”
Section: Discussionsupporting
confidence: 78%
“…This particular phenomenon -a hallmark of mammalian Bax action -has been demonstrated following Bax expression in yeast (Manon et al, 1997). To date, several studies of mammalian Bcl-2 family proteins in S. cerevisiae have focused on genetic analyses of Bax, Bcl-xL and Bcl-2, while this model has rarely been used, if at all, to characterize further members such as Bak, Bcl-w, and Mcl-1 for instance (Bodrug et al, 1995;Tao et al, 1997;Beaumont et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As the survival of different cancer cells depends on different specific antiapoptotic proteins, an easy method for testing the effect of these compounds in vivo, in system with individual antiapoptotic Bcl-2 family members, appears to be very useful. The effect of several BH3-mimetic compounds was tested in yeast cells coexpressing Bax together with different individual antiapoptotic proteins of the Bcl-2 family including Bcl-XL, Bcl-2, Bcl-w, Mcl-1 [81]. Two of tested drugs (ABT-737 and ABT-263) were shown to inhibit cell growth both on solid and liquid media in Bcl-2 family protein-dependent manner.…”
Section: Anticancer Drugsmentioning
confidence: 99%